2010
DOI: 10.1002/adfm.200901846
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Structural Damage in Human Erythrocytes Exposed to Silver, Gold, and Platinum Nanoparticles

Abstract: Human erythrocytes or red blood cells (RBCs), which constitute 99% of blood cells, perform an important function of oxygen transport and can be exposed to nanoparticles (NPs) entering into the human body during therapeutical applications involving such NPs. Hence, the haemocompatibility of the Ag, Au, and Pt NPs on human RBCs is investigated. The parameters monitored include haemolysis, haemagglutination, erythrocyte sedimentation rate, membrane topography, and lipid peroxidation. The findings suggest that pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 27 publications
5
103
0
3
Order By: Relevance
“…50,67 Our observation of changed erythrocyte shape is partly consistent with the findings of Han et al, 35 ie, that the surface charge on NPs is the dominant factor influencing their hemocompatibility, but the findings of our study suggest that the sizes of NPs and their agglomerates also play an important role. In addition, Asharani et al 34 reported that the low degree of surface deposition of NPs on the membrane of RBCs can be accompanied by significant alterations in membrane topography. In this connection, we observed NP agglomerates on the surface of RBCs (Figures S8 and S9, Tables S7 and S8).…”
Section: Mlvs After Incubation In Np Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…50,67 Our observation of changed erythrocyte shape is partly consistent with the findings of Han et al, 35 ie, that the surface charge on NPs is the dominant factor influencing their hemocompatibility, but the findings of our study suggest that the sizes of NPs and their agglomerates also play an important role. In addition, Asharani et al 34 reported that the low degree of surface deposition of NPs on the membrane of RBCs can be accompanied by significant alterations in membrane topography. In this connection, we observed NP agglomerates on the surface of RBCs (Figures S8 and S9, Tables S7 and S8).…”
Section: Mlvs After Incubation In Np Suspensionsmentioning
confidence: 99%
“…32,33 It is known that adsorption of NPs onto the surface of RBCs can change cell morphology and erythrocyte sedimentation rate, agglutination of RBCs, and hemolysis. 1,18,27,[34][35][36][37][38][39] An interesting question is whether mechanisms revealed by experimental studies of artificial membranes or computer simulations of interactions between NPs and artificial lipid membranes can also explain the interactions of NPs with biological membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the particle concentration and incubation time, the distribution and uptake rate of silver nanoparticles into the cells vary. The 2D maps in Figures 13.5a-c show a high quantity of 107 Ag in the perinuclear region of the cells, which is in contrast to the 3 h-exposure where the particles are homogenously distributed in the cytoplasm. Only low signal intensity was found in the nucleus region since nanoparticles above 20 nm could not enter through the nuclear membrane.…”
Section: Quantification Of Metal Nanoparticles In Cellsmentioning
confidence: 57%
“…Owing to the high spatial resolution of LA-ICP-MS, silver nanoparticles are visualized with respect to the cellular ultrastructure of fibroblast cells under different incubation conditions. In Figure 13.6 the overlay of the color encoded 107 Ag + local intensity maps with bright field micrographs is shown for three nanoparticle concentrations and two incubation times. Depending on the particle concentration and incubation time, the distribution and uptake rate of silver nanoparticles into the cells vary.…”
Section: Quantification Of Metal Nanoparticles In Cellsmentioning
confidence: 99%
See 1 more Smart Citation